TFIID dependency of steady-state mRNA transcription altered epigenetically by simultaneous functional loss of Taf1 and Spt3 is Hsp104-dependent - Ryo Iwami; Naoki Takai; Minenosuke Matsutani; Yuh Shiwa; Haruki Kokubo; Koji Kasahara; Tetsuro Kokubo (PLoS ONE, 2023)
In Saccharomyces cerevisiae, class II gene promoters have been divided into two subclasses, TFIID- and SAGA-dominated promoters or TFIID-dependent and coactivator-redundant promoters, depending on the experimental methods used to measure mRNA levels. A prior study demonstrated that Spt3, a TBP-delivering subunit of SAGA, functionally regulates the PGK1 promoter via two mechanisms: by stimulating TATA box-dependent transcriptional activity and conferring Taf1/TFIID independence. However, only the former could be restored by plasmid-borne SPT3. In the present study, we sought to determine why ectopically expressed SPT3 is unable to restore Taf1/TFIID independence to the PGK1 promoter, identifying that this function was dependent on the construction protocol for the SPT3 taf1 strain. Specifically, simultaneous functional loss of Spt3 and Taf1 during strain construction was a prerequisite to render the PGK1 promoter Taf1/TFIID-dependent in this strain. Intriguingly, genetic approaches revealed that an as-yet unidentified trans-acting factor reprogrammed the transcriptional mode of the PGK1 promoter from the Taf1/TFIID-independent state to the Taf1/TFIID-dependent state. This factor was generated in the haploid SPT3 taf1 strain in an Hsp104-dependent manner and inherited meiotically in a non-Mendelian fashion. Furthermore, RNA-seq analyses demonstrated that this factor likely affects the transcription mode of not only the PGK1 promoter, but also of many other class II gene promoters. Collectively, these findings suggest that a prion or biomolecular condensate is generated in a Hsp104-dependent manner upon simultaneous functional loss of TFIID and SAGA, and could alter the roles of these transcription complexes on a wide variety of class II gene promoters without altering their primary sequences. Therefore, these findings could provide the first evidence that TFIID dependence of class II gene transcription can be altered epigenetically, at least in Saccharomyces cerevisiae.